Isolamento e avaliação da atividade biológica dos alcalóides majoritários de Tabernaemontana angulata Mart. ex Müll. Arg., Apocynaceae - de Assis, Camila M. [UNESP]; Moreno, Paulo R. H.; Marx Young, Maria Claudia; de Arruda Campos, Ivan P. [UNESP]; Suffredini, Ivana B. [UNESP] (John Benjamins Publishing Company, 2009)
"Isolation and evaluation of the biological activity related to the major alkaloids in Tabernaemontana angulata Mart. ex Mull Arg., Apocynaceae." Introducing-new chemotherapeutic agents is a, great demand. in the control of infections diseases.' Brazil is one of the richest countries in biodiversity and the Laboratorio de Extracao at UNIP has been collecting plants from. the Amazon and Atlantic Rain Forests with the aim of screening for new antibacterial and antitumor plant extracts. Previous studies demonstrated that the ethanol fraction obtained from the crude extract of Tabernaemontana angulata stems showed antibacterial activity against Staphylococcus aureus (ATCC 6538 in the microdilution broth assay. Two alkaloids were the major compounds in the active fraction, verified by thin layer chromatography analysis. In the present study, the total alkaloids were obtained from the crude extract and were fractionated by preparative thin layer chromatography for the isolation of the main components. The isolated. compounds were identified by GC/MS and (1)H-NMR as coronaridine,e and voacangine. The alkaloid fractions obtained from the isolation procedure were tested for antibacterial activity, but no activity was detected.
Isolation and evaluation of the biological activity related to the major alkaloids in Tabernaemontana angulata Mart. ex Mull. Arg., Apocynaceae
Keywords: Tabernaemontana angulata; Apocynaceae; alkaloids; antibacterial activity; cytotoxicity